Replanting a plane with level lines as a rational approach to solving problems of descriptive geometry - Rihsibaeva Н. Рихсибаева X.; Yedylbaev U. Едылбаев У.Д. (Рroblems of engineering and professional education, 2022)
The article discusses the best ways to solve positional and metrical problems of descriptive geometry. If any plane can be specified with its own level lines, i.e. horizontal and frontal, the solutions of many positional and metric problems are simplified. According to the authors, this approach will allow students to successfully apply the best ways to solve positional and metrical problems and increase their level of spatial thinking.